(untitled) (Journal of the College of Basic Education, 2022)
Due to the exposure of some cities to flooding during the rains during the past years and the scarcity of water in the cities, this prompted us to think about searching for solutions to this problem, which began to disturb the society and the executive authorities. On this basis, the aim of this research is to propose solutions that help the executive authorities in facing the rainfall by finding a system for harvesting that water without causing any problem of flooding, which contributes to the stability of the community and the non-disruption of its properties.